Kajian Prinsip Estetika Pada Bangunan Masjid Jami Al-Baakhirah - Resti Atsila, Rifka; Kurnia, Rachmat; Hidayah R, By Nur; Abrianti S , Tine; Sekatia, Augi (CV RIFAINSTITUT, 2025)
The building of Jami Al-Baakhirah Mosque is a mosque with a unique form and facade, resembling a ship, and holds a high aesthetic value. This research aims to analyze the application of aesthetic principles to the facade and form of the building, as well as how the design maintains the fundamental architectural principles of a mosque. The research method used is qualitative descriptive, with primary data collected through field observations, documentation, and questionnaires, along with secondary data from literature studies. The aesthetic analysis is conducted using a structured approach, assessing aspects of unity, balance, rhythm, ornamentation, and contrast, referring to the aesthetic theory of D.K. Ching in his book Architecture: Form, Space, and Order as well as the architectural principles of Vitruvius. The results show that the building of Jami Al-Baakhirah Mosque reflects aesthetic values through the unity of design concepts, dynamic asymmetric balance, static and dynamic rhythm, and contrast between design concepts, function, and visual elements. This study also shows that this building is able to fulfill the architectural principles of a mosque with its relevant aesthetic principles.